A evasão escolar: uma perspectiva dos atendimentos do conselho tutelar regional leste de Cascavel/Pr. - Silveira, Monica Andressa (2016)
This study has examined the number of teenagers who have dropped out of the school system in 2014, the causes that have led them to drop it out and what kind of interference that have gone through from social, economic and political contexts. These facts allow us to understand the increasing renouncement by children and adolescents from the schools. Thus, this research aimed at evaluating whether the actions taken by the Council Guardianship from Eastern Regional of Cascavel/PR were effective and gave the teenager's a chance to return to the classroom. As a means to understand this phenomenon, a survey was carried out, whose methodology was qualitative-quantitative. The documents of both Prevention and Combating Dropouts (PPCEE) and official documents (letters, reports, referrals, reference sheets and counter-references) were analyzed and registered by the Guardianship board members when they intervened on those families and teenagers at the council headquarters. Mainly, when, for some reason, they have dropped out even for a certain period the classroom. This research has shown us that there are many aspects concerning School Dropouts and that there are several determinants as well. School dropout is considered the gateway to other violations of law that is not only education. It comes as a warning that something is wrong. It enables intervention, resistance to schooling by adolescent as other forms of violence that the student may be experiencing. Finally, it was possible to formulate some considerations that can help the educational institution, such as the program to prevent and combat absenteeism and the Guardian Council to act out preventively in cooperation arrangements to ensure the reparation for the right to education.